New Perspectives on Corporate Social Responsibility Locating the Missing Link - O'Riordan, Linda.; O'Riordan, Linda.; Zmuda, Piotr.; Zmuda, Piotr.; Heinemann, Stefan.; Heinemann, Stefan. (FOM-Edition, FOM Hochschule für Oekonomie & Management, 2015)
Providing a timely contribution to the ongoing questions surrounding topics which are by definition subject to varying stakeholder interpretations, this book addresses "the missing link" between theoretical CSR concepts and everyday management practice. It acts as a guide to awaken managers to the advantages of adopting a CSR "mindset" when developing sustainable business strategies. The book consists of three parts: 1) A theoretical realm which establishes the key concepts and rationale for the adoption of a sustainable CSR approach, 2) A practical realm which addresses putting CSR and sustainability into business practice, 3) An educational realm which proposes how to incorporate the concepts into teaching and training. Contents Theoretical realm Practical realm Educational realm The Editors Linda O’Riordan is a Professor of Business Studies and International Management and Director of the KompetenzCentrum for Corporate Social Responsibility (KCC) at the FOM University of Applied Sciences (FOM), Essen, Germany. She researches, writes, and lectures on responsible management and sustainable entrepreneurship with a focus on an inclusive approach to organising business in society. Piotr Zmuda is a Professor of Business Studies and International Management and a Research Associate of the KompetenzCentrum for Corporate Social Responsibility (KCC) at the FOM University of Applied Sciences (FOM), Essen, Germany. He teaches Master's and Bachelor's students in Corporate Governance and Corporate Social Responsibility (CSR), International Management, Strategic Management, and Management Consulting. Stefan Heinemann is a Professor and Vice-Rector for Cooperations and Sustainability Representative at the FOM University of Applied Sciences (FOM), Essen, Germany. He is also a committed member of the work group "tertiary institutions" of the UNESCO World Decade of Education for Sustainable Development, Director of Business Ethics at the FOM KCC KompetenzCentrum für Corporate Social Responsibility and Member of the Board of Trustees of sneep - student network for ethics in economics and practice.  .